KAJIAN MUTU ARANG HASIL PIROLISIS CANGKANG KELAPA SAWIT - Abdul Gani Haji (Purifikasi, 2010)
Oil palm shell waste has a hard structure and is difficult to biodegrade. Pyrolisis is a suitable and profitable technique for destruction of this waste. Using this technique, the oil palm shell waste can be degraded quickly and the product can be used for various purposes. The aim of this research was to find out the quality of charcoal as a pyrolysis product of the oil palm shell waste. The pyrolisis took place about 5 hours in a drum reactor, which was equipped with temperature controller device of thermocouple brand. The structure of charcoal product was characterized by Furier Transform Infra Red (FTIR) and Scanning Electron Microscope (SEM). The chemical composition was identified by py-GCMS. The average charcoal product was 38.81% (w/w). The charcoal contained 4.02% of water, 20.44% of fly materials, 17.46% of ash, 62.10% of fixed carbon, and calorific value of 6,118 calories/g. The FTIR analysis showed that the charcoal contained -OH, -C=O, and -C-H aromatic functional groups. Results of SEM analysis indicated that the charcoal had many pores, which were covered by impurities. The py-GCMS identified that the charcoal was composed of 25 compounds. Since quality standards for this type of charcoal was not available, it was compared to the quality standards of coconut shell charcoal powder according to SNI-06-4369-1996. It was found that the palm shell charcoal quality was low. However, based on the characterization results, it would still be profitable to produce briquettes and active carbon from the palm shell charcoal.